2007
DOI: 10.1111/j.1540-4609.2007.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of GPA on Perceived Improvement of Higher‐Order Cognitive Skills*

Abstract: Colleges of Business (COBs) have experienced high growth rates in the past decade and many colleges are imposing minimum grade point average (GPA) requirements for students to enter or remain in the college. A primary reason for this requirement may be the belief that students with high GPAs are more inclined to demonstrate higherorder cognitive skills (HOCS) than students with low GPAs. It is not clear whether the link is valid. This study hypothesizes that students with high GPAs who are taught in the same w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Earlier studies suggest that multimedia case studies are a major contributor to improvements in the quality of learning in technical classrooms (Bradley, Sankar, Clayton, Mbarika, & Raju, 2007b; Mbarika, Sankar, & Raju, 2003a; Mbarika, Sankar, Raju, & Raymond, 2001; Sankar & Raju, 2002). To support this conclusion, several studies have evaluated the use of multimedia instructional materials in IT undergraduate classrooms and found the students’ responses to be favorable (Bradley et al, 2007b; Mbarika et al, 2003a; Sankar & Raju, 2002). Additionally, those studies identified the following advantages and strengths of the multimedia case study approach:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies suggest that multimedia case studies are a major contributor to improvements in the quality of learning in technical classrooms (Bradley, Sankar, Clayton, Mbarika, & Raju, 2007b; Mbarika, Sankar, & Raju, 2003a; Mbarika, Sankar, Raju, & Raymond, 2001; Sankar & Raju, 2002). To support this conclusion, several studies have evaluated the use of multimedia instructional materials in IT undergraduate classrooms and found the students’ responses to be favorable (Bradley et al, 2007b; Mbarika et al, 2003a; Sankar & Raju, 2002). Additionally, those studies identified the following advantages and strengths of the multimedia case study approach:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We selected these five learning outcomes because they are the desired learning outcomes for the introductory IT course at the university where the study took place. Furthermore, prior research highlights the importance of these learning outcomes in explaining the impact of both lecture and multimedia not only in improving students’ ability to identify, integrate, evaluate, and interrelate technical concepts, but also in enhancing their critical thinking, decision‐making, and problem‐solving skills (Bradley et al, 2007b; Mbarika et al, 2003a). Also, these learning outcomes consistently appear at the top of lists of hiring criteria (Duke, 2002).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Atwater and Pittman (2006) wrote that decision making in the business arena is very complex. Researchers King (2000), Bradley, Sankar, Clayton, Mbarika, and Raju (2007) believe that for students to be successful in the workforce, it is critical that their education helps them reason, think critically, and improve problem‐solving skills.…”
Section: Introductionmentioning
confidence: 99%
“…In recognition of the challenges facing statistics instructors, researchers have focused on creating new instructional materials to address the statistical needs of business students. At the same time, educational innovators have been emphasizing how critical it is for the business students to be exposed to business applications when learning to master the core material (Mbarika et al 2003, Bradley et al 2007. Some textbook writers (e.g., Anderson et al 2009, Berenson et al 2006) have begun to address both of these requirements, i.e., to prepare the students on statistics fundamentals and to expose them to business applications.…”
Section: Introductionmentioning
confidence: 99%